From Peirce to Skolem : a neglected chapter in the history of logic - Brady, Geraldine (Studies in the history and philosophy of mathematics, 2000)
This book is an account of the important influence on the development of mathematical logic of Charles S. Peirce and his student O.H. Mitchell, through the work of Ernst Schroder, Leopold Lowenheim, and Thoralf Skolem. As far as we know, this book is the first work delineating this line of influence on modern mathematical logic.